A novel endoplasmic reticulum-targeted ratiometric fluorescent probe based on FRET for the detection of SO2 derivatives. (April 2021) - Li, Zhang-Yi; Cui, Xiao-Ling; Yan, Ye-Hao; Che, Qiao-Ling; Miao, Jun-Ying; Zhao, Bao-Xiang; Lin, Zhao-Min
Abstract: A novel FRET-based fluorescence probe, NBIS, constructed by benzoindole-based hemicyanine as an acceptor and naphthalimide derivatives as a donor was developed for the detecting of sulfur dioxide (SO2 ) derivatives. Probe NBIS exhibited high energy transfer efficiency (89%) and showed high sensitivity (LOD: 16.2 nM) toward HSO3 − /SO3 2− . Probe NBIS could target the endoplasmic reticulum (ER) and was applied to image exogenous and endogenous HSO3 − /SO3 2− in living cells. Graphical abstract: Image 1 Highlights: A novel fluorescence probe NBIS, composed from a benzoindole-based hemicyanine and naphthalimide derivative was designed. Probe NBIS showed high sensitivity (LOD: 16.2 nM) toward HSO3 − /SO3 2− . Probe NBIS exhibited high energy transfer efficiency (89%). Probe NBIS was applied to image exogenous and endogenous HSO3 − /SO3 2− in the living cells. Probe NBIS could target the endoplasmic reticulum well in cell imaging.